Manajemen Resiko Bank Syariah Terhadap Pembiayaan Bagi Hasil (Pendekatan Normatif) - Hasan Hasan (IAIN Ambon, 2017)
Implementation of risk management in Islamic Bank to finance for the results, conducted through risk identification, risk measurement, and monitoring risks to Character (or the nature of the customer decision-loan), Capacity (the client's ability to run the business, and return the loans taken as scheduled ), capital (the amount of capital required the borrower), collateral (collateral which has been owned by a borrower to the bank), and Condition (state business prospects or clients or not). So the bank can avoid a general risk, ie credit risk, market risk, liquidity risk, operational risk, legal risk (legal), reputation risk, strategic risk and compliance risk (compliance). While the normative approach to risk management of Islamic banks in the financing for the results, more directed to the mudaraba financing and Musharaka, carried out based on the guidelines on the Koran, the Hadith, the operational rules fiqhi dilakasanakan based National Sharia Board Fatwa Council of Ulama Indonesia and Bank Indonesia regulations about risk management. Risk management in order to work well, the bank manager should disseminate the principles of the implementation to the financing funds for the result on the one hand, and here's another Islamic banking managers are required to improve its human resources in carrying out risk management in a professional manner. Keywords: risk management, Islamic banks, financing for results